Food engineering handbook. Food engineering fundamentals - Varzakas, Theodoros; Tzia, Constantina (2015)
"This book provides an up-to-date review of food processing and engineering phenomena. It addresses the basic principles of food engineering technologies used in food processing operations around the world, combining theory with a practical hands-on approach. The book explores the basic and applied aspects of food engineering from mass transfer and heat transfer to steam and boilers, heat exchangers, fluid flow, and novel food processes such as membrane technology. It describes the physico-chemical and microbiological methods for each preservation methodology and addresses interactions between different food constituents"--
"Preface It is an innovative piece of work coming in a two-volume set bringing together aspects of food engineering and food process engineering phenomena and operations. This handbook provides a stimulating and up-to-date review of fundamental food engineering phenomena. An in-depth coverage of the major technologies compared with the broader coverage of others will be the deciding factor for would-be purchasers or academics considering prescribing the book as a food engineering textbook. It addresses the basic principles of food engineering methods used in food processing operations around the world. While it covers the theory it combines this with a practical hands-on approach. The book is a comprehensive resource that explores the basic and applied aspects of food engineering from mass transfer and heat transfer to steam and boilers, heat exchangers, diffusion, absorption, evaporation, and novel food processes such as irradiation technology. In each chapter the addition of case studies and problem calculation is highlighted and this makes the key difference between other textbooks on food engineering. This volume, along with Food Process Engineering, comprises the two-volume set Food Engineering Handbook, and can be sold individually or together as a set. KEY FEATURES OF THIS BOOK The book provides an essential and complete reference on the modeling, quality and safety, and technologies associated with food engineering. It explains the interactions between different food constituents that might lead to changes in food properties"--
Includes bibliographical references and index.
Keywords: Food industry and trade; Food -- Biotechnology; TECHNOLOGY & ENGINEERING / Food Science